Isotropic modelling and blast analysis of heritage structure. (2022) - Raza, Ismail; Shamim, Saba; Ahmad, Shakeel; Khan, Rehan A.
Abstract: The protection and conservation of heritage structures are of foremost importance. Hence, the present study focuses on the isotropic modelling of a heritage school building, to determine its response to the action of various blast scenarios. The impact due to blast explosion may result in severe damage to any structure especially those made of brick masonry. The heritage building under study is an unreinforced masonry structure that by its inherent nature is extremely weak in out-of-plane loading such as; blast. The considered building has been modelled in STAAD Pro using finite element macro-modelling approach. The idealised blast pressure–time histories have been developed using IS: 4991-1968 (Reaffirmed 2018). Nodal Force application method has been implied to apply corresponding blast load on the structure at varying standoff distances.